Manajemen Humas dengan Dunia Industri Otomotif dalam Meningkatkan Mutu Pendidikan di SMK Ma’arif 1 Kroya - Zidni Choiron Nafi; Muh Hanif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to investigate the role of public relations management in establishing cooperation with the automotive industry to improve the quality of education at SMK Ma'arif 1 Kroya Cilacap. The research method used is a case study with a qualitative approach. Data were collected through in-depth interviews with the Principal, the Head of Public Relations at SMK Ma’arif 1 Kroya, and representatives from the automotive industry involved in the cooperation program. The research results show that public relations management plays an important role in forming and maintaining good relationships between the school and the automotive industry. Through promotional efforts, effective communication, and careful negotiation, public relations management has successfully established mutually beneficial partnerships for both parties. Public relations management at SMK Ma’arif 1 Kroya has successfully created mutually beneficial partnerships with various stakeholders, including the community and companies. This cooperation has brought various benefits, including improving the quality of education for students at SMK Ma'arif 1 Kroya Cilacap. The implementation of cooperation at SMK Ma’arif 1 Kroya, represented by the Head of Public Relations, with automotive industry companies includes MoUs with companies, industry visits, industrial internships, student and teacher apprenticeships, integration of the school curriculum with industry needs, training and certification for teachers, as well as the development of facilities and educational infrastructure that meet the demands of the automotive industry. All these efforts contribute to enhancing the quality of learning and preparing students to enter the workforce. This research concludes that effective public relations management with the automotive industry can be an effective strategy for improving the quality of education at SMK Ma'arif 1 Kroya Cilacap. The practical implication of this research is the importance of the role of public relations management in building and maintaining sustainable relationships with external stakeholders to support the school's mission and vision.